Analisis pergeseran sektor unggulan Kabupaten Tanjung Jabung Barat - Alex Salenko Munthe; Zulgani Zulgani; Hardiani Hardiani (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
The purpose of this research is to analyze the shifts that occur to the three leading sectors in the Regency of West Tanjung Jabung and to find out how much contribution from the three leading sectors to the economic growth during the period 2011-2015. The data collection method used in this research is secondary data analysis which is collecting data through the material of the library. From based on the result of data analysis, the result of the shift of the three leading sectors of the economy Tanjung Jabung District West during 2011-2015 using shift-share analysis changed at the national level (Ns) of 3,851,361.79, with a differential shift (D) value of -34,748.82 and proportional shift (P) value of -295,710.45, where the value of shifting the three leading sectors experienced development in the period 2011-2015 amounted to 3,520,902.92. The three leading sectors are classified into the analysis of Typology Klassen to determine the value of its contribution to the growth rate of the region, where the mining and quarrying sectors become the first quadrant, the manufacturing sector becomes the second quadrant, and then the agriculture, forestry, and fishery sectors become the third quadrant. Keywords: Leading sector, Shift-share, Typology klassen, Economic growth.